Uji Mekanik Bata Ringan Berbahan Dasar Limbah Pengolahan Emas dengan Variasi Limbah Batu-bara dan Semen - Wathoni, Muhammad Munawir; Prasetya, Dwi Sabda Budi; Pangga, Dwi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2018)
[Title: The Mechanical Test of Lightweight Brick Made from Gold Processing Waste with Variations in Coal and Cement Waste]. The purposes of this research are to make lightweight concrete using waste processing of gold with variation fly ash and cement the better than conventional concrete. The value of this research has tested mechanics which comprises density, porosity and strength. The research has done with some stage are: 1) Make lightweight concrete using LPE with variation fly ash and cement. 2) Characterization of the samples which comprise density, porosity and the strength, 3) Analysis of tested mechanical lightweight concrete. The value of lightweight concrete to make with variation composition fly ash and cement in a series are: (0/100), (5/95), (10/90), (15/85), (20/80) who are in volume. To make lightweight concrete with composition foam and water controlled as much as 10 ml and 150 ml at all of the sample. So we get the density value of lightweight concrete without fly ash is 1.61. In lightweight concrete with fly ash, we get the minimum density of lightweight is 1.15. The porosity value of lightweight concrete without fly ash is 13.6%, and the porosity value of lightweight concrete with fly ash is 8.0%. The compressive strength of lightweight concrete without fly ash is 1.629 MPa and the compressive strength of lightweight concrete with fly ash is 1.772 MPa. The value shown to process waste processing of gold with variation fly ash and cement to be lightweight concrete can get mechanical in character of lightweight to be better than conventional concrete.